2004
DOI: 10.3727/000000004783983990
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Xenotransplantation of GFP Mouse Bone Marrow Stromal Cells in Intact and Stroke Rat Brain: Graft Survival and Immunologic Response

Abstract: The present study characterized survival and immunologic response of bone marrow stromal cells (BMSCs) following transplantation into intact and stroke brains. In the first study, intrastriatal transplantation of BMSC (60,000 in 3 µl) or vehicle was performed in normal adult Sprague-Dawley male rats that subsequently received daily cyclosporin A (CsA, 10 mg/kg, IP in 3 ml) or vehicle (olive oil, similar volume) starting on day of surgery up to 3 days posttransplantation. Animals were euthanized at 3 or 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 81 publications
4
28
0
Order By: Relevance
“…Previous studies show that the BMSCs survive in the ischemic brain, and specifically migrate into the ischemic boundary zone (IBZ) after transplantation (Chen et al, 2001;Irons et al, 2004;Lee et al, 2003;Li et al, 2002). Administration of BMSCs reduces neuronal apoptosis (Chen et al, 2003a), promotes angiogenesis (Chen et al, 2003b), synaptogenesis (Zhang et al, 2006) and neurogenesis (Chen et al, 2004) associated with cerebral ischemia in adult rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the BMSCs survive in the ischemic brain, and specifically migrate into the ischemic boundary zone (IBZ) after transplantation (Chen et al, 2001;Irons et al, 2004;Lee et al, 2003;Li et al, 2002). Administration of BMSCs reduces neuronal apoptosis (Chen et al, 2003a), promotes angiogenesis (Chen et al, 2003b), synaptogenesis (Zhang et al, 2006) and neurogenesis (Chen et al, 2004) associated with cerebral ischemia in adult rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite controversies, immunosuppressive treatment may be a key determinant for homing of HUCB cells i.v. infused into rats (31). Several investigations suggest that T cell-mediated immune reaction plays a significant role in graft rejection and that interspecies incompatibility contributes significantly to phagocytosis of xenogeneic cells (32).…”
Section: Figure 2 (A)mentioning
confidence: 99%
“…11 Potential advantages of MSCs over other types of transplanted cells are shown in Table 1 which include their ability to be harvested from autologous donors, their relatively rapid expansion ex vivo and the possibility that allogeneic MSCs are nonimmunogenic and, hence, readily available for clinical use, 12 although some studies have indicated that immune suppression improves transplant survival. [13][14][15] Thus, they have been identified as promising candidates in the treatment of CNS injury.…”
Section: Introductionmentioning
confidence: 99%